2012
DOI: 10.1101/gad.180968.111
|View full text |Cite
|
Sign up to set email alerts
|

A monocarboxylate transporter required for hepatocyte secretion of ketone bodies during fasting

Abstract: To find new genes that influence liver lipid mass, we performed a genetic screen for zebrafish mutants with hepatic steatosis, a pathological accumulation of fat. The red moon (rmn) mutant develops hepatic steatosis as maternally deposited yolk is depleted. Conversely, hepatic steatosis is suppressed in rmn mutants by adequate nutrition. Adult rmn mutants show increased liver neutral lipids and induction of hepatic lipid biosynthetic genes when fasted. Positional cloning of the rmn locus reveals a loss-of-func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
123
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 48 publications
(53 reference statements)
3
123
0
Order By: Relevance
“…Two promising candidates for facilitated ketone transporter are MCT isoforms 1 (MCT1, encoded by Slc16a1) and 7 (MCT7, encoded by Slc16a6), both of which are known to transport ␤-HB (12,15). Although MCT1 is expressed exclusively at the RPE apical membrane and enriched at the photoreceptor inner segment (16), MCT7 expression in the RPE and retina has not been studied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two promising candidates for facilitated ketone transporter are MCT isoforms 1 (MCT1, encoded by Slc16a1) and 7 (MCT7, encoded by Slc16a6), both of which are known to transport ␤-HB (12,15). Although MCT1 is expressed exclusively at the RPE apical membrane and enriched at the photoreceptor inner segment (16), MCT7 expression in the RPE and retina has not been studied.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to intracellular metabolites, we also analyzed the Ringer's solution in the apical and basolateral compartments of these hfRPE for 13 C metabolites. We found that hfRPE cells incubated with [1][2][3][4][5][6][7][8][9][10][11][12][13] C]palmitate alone released significantly more (7-fold) labeled ␤-HB (75.2 Ϯ 49.7 pmol/cm 2 RPE in a 500-l volume over 3 h) into the apical chamber compared with the basal chamber (10.5 Ϯ 18.3 pmol/cm 2 RPE in a 1500-l volume over 3 h) (Fig. 3E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although functional investigations have yet only been performed in zebrafish,11 this study provides first evidence for a contribution of MCT7 in hepatic lipid metabolism by secreting ketone bodies, especially β‐hydroxybutyrate. Zebrafish mutants with hepatic steatosis were identified to harbor a loss‐of‐function mutation in the slc16a6 locus, which causes lipid accumulation in fasted livers.…”
Section: Ophthalmological Diseasesmentioning
confidence: 85%
“…Human MCT7 has not yet been systematically characterized. Mct7/s lc16a6 from zebrafish has been demonstrated to selectively export ketone bodies from the liver, especially β‐hydroxybutyrate, and transgenic expression of human SLC16A6 rescued a mutant s lc16a6 zebrafish phenotype with hepatic steatosis, indicating a similar function for human MCT7 11. MCT11 has recently been shown to mediate H + ‐coupled transport of pyruvate, indicating similar substrate specificities as MCT1–MCT4; however, transport of other monocarboxylates was not tested.…”
Section: Substrates Of Mct Transportersmentioning
confidence: 99%